2007
DOI: 10.1890/06-0869
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Historic Demography of an Endangered Seabird

Abstract: Abstract. Reducing extinction risk for threatened species requires determining which demographic parameters are depressed and causing population declines. Museum collections may constitute a unique, underutilized resource for measuring demographic changes over long time periods using age-ratio analysis. We reconstruct the historic demography of a U.S. federally endangered seabird, the Marbled Murrelet (Brachyramphus marmoratus), from specimens collected ;100 years ago for comparison with predictions from compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The principal advantage of using museum collections for comparative demographic studies is the potential availability of information from a wide range of species and regions for which mark-recapture studies are impractical. Although not pursued in this study, museum collections also provide historical data that can be used to examine changes in survival over time (e.g., Beissinger and Peery 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The principal advantage of using museum collections for comparative demographic studies is the potential availability of information from a wide range of species and regions for which mark-recapture studies are impractical. Although not pursued in this study, museum collections also provide historical data that can be used to examine changes in survival over time (e.g., Beissinger and Peery 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation biologists try to identify factors that cause species' decline so they can develop management prescriptions for their recovery (Beissinger & Peery 2007). Our analysis emphasizes the role of local grey sources to reconstruct the historical demographic collapse of populations on a large time span.…”
Section: Discussionmentioning
confidence: 99%
“…The reconstructions of demographic collapses within scientific literature are recently available only for few species (Clarke et al 1988;Dennis et al 1991;Peterman et al 2003;Bivings 2006;Cox et al 2006;Beissinger & Peery 2007). Therefore, at least in the European context, the large availability of bibliographic sources starting from the Middle Ages, represents an opportunity to reconstruct the historical trends of large mammal and bird populations for which many anecdotic data are available.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show a stark contrast between proportional sensitivity and natural variability of vital rates for a wide range of species (Beissinger & Peery, ; Citta & Mills, ; Hoekman, Mills, Howerter, Devries, & Ball, ; Manlik et al., ; Mitchell, Pacifi, Grand, & Powell, ; Norris & McCulloch, ; Taylor et al., ). For example, in ungulate populations, adult survival consistently had the highest elasticity, but showed low temporal variability (Gaillard, Festa‐Bianchet, & Yoccoz, ).…”
Section: Caveats and Limitations To Proportional Sensitivity Analysismentioning
confidence: 99%
“…One example which illustrates that proportional sensitivity is not necessarily the best indicator for effectiveness of wildlife management actions is a study on a marbled murrelet ( Brachyramphus marmoratus ) (Order: Charadriiformes; Family: Alcidae) population in California. From 1892 to 1922, reproductive rates declined 8‐ to 9‐fold, while adult survival remained comparatively constant (Beissinger & Peery, ). Despite that growth rate was relatively insensitive to proportional changes in reproduction (Peery, Becker, & Beissinger, ), a life‐table response experiment (LTRE; see Data ) showed that historic reproductive rates would support stable populations, but contemporary rates would result in population declines (Beissinger & Peery, ).…”
Section: Caveats and Limitations To Proportional Sensitivity Analysismentioning
confidence: 99%